Mathematical modeling of the effect of internal combustion engine parameters on vehicle acceleration dynamics (Международный научный журнал «Инженер», 2026)
Mathematical model has been calculated in the study, which determines the relationship between the engine's operating process and the dynamics of the car. The adequacy of the model was verified using an experimental study of the B15D2 engine to obtain adjustment, load and external speed characteristics.